Imatinib induces sustained progression arrest in RECIST progressive desmoid tumours: Final results of a phase II study of the German Interdisciplinary Sarcoma Group (GISG) - Kasper, Bernd; Rauch, Geraldine; Limprecht, Ronald; Sommer, Michaela; Dimitrakopoulou-Strauss, Antonia; Pilz, Lothar R.; Hohenberger, Peter (European journal of cancer, 2017)
Background Desmoid tumours describe a rare monoclonal, fibroblastic proliferation characterised by an often unpredictable clinical course. Surgery is one therapeutic option for progressing patients, except if mutilating and associated with considerable function loss. Different systemic treatment approaches have been investigated and promising results could be demonstrated using imatinib. Patients and methods We initiated a phase II trial within the German Interdisciplinary Sarcoma Group (GISG) evaluating imatinib to induce progression arrest in desmoid tumour patients being Response Evaluation Criteria in Solid Tumours (RECIST) progressive, not amenable to surgical resection with R0 intent or accompanied by unacceptable function loss (NCT01137916). Thirty-eight patients (median age 44 years [range: 19-80]; 68% female; 90% Eastern Cooperative Oncology Group (ECOG) performance status 0) were treated with a daily dose of 800 mg imatinib planned over 2 years. The progression arrest rate after 6 months of imatinib treatment (PAR6mo) was the primary end-point. Patients showing disease progression under imatinib could be treated with nilotinib 800 mg daily. Accrual started in July 2010 in four GISG centres and finalised in September 2013. Results The final analysis for the primary end-point in the evaluable patients of the full analysis set revealed a PAR6mo of 65%. Subsequent progression arrest rates at 9, 12, 15, 18, 21 and 24 months were 65%, 59%, 53%, 53%, 50% and 45%, respectively. None of the patients died within the study observational period. Best reported response was seven partial responses at 21 months revealing an overall response rate of 19%. Eight patients treated with nilotinib demonstrated a PAR at 3 months of 88% (7/8); no more disease progressions occurred until end of study. In general imatinib adverse events were mild to moderate. Conclusions Imatinib induces sustained progression arrest in RECIST progressive desmoid tumour patients. In addition, nilotinib had the potential to stabilise desmoid tumour growth after treatment failure with imatinib.